Método de produção de nanocompósitos funcionais e produtos obtidos - Job, Aldo Eloizo [UNESP]; Budemberg, Eduardo Roque; Bellucci, Felipe Silva; Salmazo, Leandra Oliveira; Nobre, Marcos Augusto de Lima [UNESP] (Instituto Nacional de Propriedade Industrial (INPI), 2013)
The patent application relates to the method for producing functional nanocomposites made of paramagnetic nanoparticles with Ni0.5Zn0.5Fe2O4 stoichiometry and to the thus obtained product. The method comprises at least the following steps: producing functional nanocomposites by the modified polyol method; mechanically blending the functional nanocomposites with natural rubber and adding vulcanising agents; and thermoforming the functional nanocomposite.
Method for Producing Functional Nanocomposites Made of Paramagnetic Nanoparticles of Ni0.5zn0.5fe2o4 and Thus Obtained Functional Nanocomposites
Processo: WO2013131159
Número de publicação: WO2013131159 (A1)
Número de aplicação: WO2013BR00066